Analisis Pengaruh Manajemen Operasi Dalam Perusahaan - Nani Qurotul A”Yun (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Operational management is part of the work process, implementation, organization, or overall management in an organization or company. Our country has experienced difficulties since the implementation of PSBB. This also has an impact on the economy in Indonesia. Every company will compete to be at the forefront to meet consumer needs in the market in order to survive in the midst of competition. The type of research conducted in the discussion of this article is by using literature studies or literature reviews, The data sources used in this study are secondary data which are types of data that come from documents or other secondary sources Several supporting aspects for the company, Project Management, Process Strategy, Quality Management, Forecasting Management, and Strategic Location.